Web-based Development: Consultation System for Depression Community - Fatin Atika Natasha Mohd Azli; Rozaida Ghazali (Applied Information Technology And Computer Science, 2023)
An abstract consultation system for depression community is a website that provides mental health support and resources to individuals struggling with depression. It offers support from trained professionals or volunteers, as well as self-help resources like informational articles and coping strategies. The website also connects individuals with similar experiences and offers referrals to local in- person therapy and other mental health services. It may also include mental health assessment tools and a crisis hotline for severe distress or suicidal thoughts. The website aims to provide support and guidance to those struggling with depression.